Preliminary analyses on detection of SYT-SSX fusion-transcripts in Synovial Sarcoma - Effendy Goon, Danial; Harun, Norra; Muhammad, Siti Aesah @ Naznin; A.Talib, Norlelawati (2012)
Introduction: Synovial Sarcoma is a rare cancer and account for 5-10% of adult soft tissue sarcomas. The tumour exhibits unspecified histogenesis composed primarily of spindle cells with variable epithelial components. Despite establishment of some immunohistochemistry staining, making a definitive diagnosis of synovial sarcoma remains a challenging task. This is due to the histo-morphology and immunophenotypes similarities of this tumour to other types of soft tissue sarcoma. Objective: The current study aims to apply a molecular method for detection of SYT-SSX fusion transcript, a common molecular defect (>90% of the cases) in Synovial Sarcoma irrespective of the histologic subtypes. Method: Paraffin-embedded fixed-tissue (PEFT) blocks of 3 confirmed and 15 possible cases of Synovial Sarcoma were retrieved from Department of Pathology, Tengku Ampuan-Afzan Hospital, Kuantan and subjected to RNA purification using the standard spin column protocol. A one step direct RT-PCR was performed using SYT-SSX and PBGD primer sets for detection of SYT-SSX fusion gene and the reference gene PBGD respectively. Results: Our preliminary molecular analyses showed positive SYT-SSX fusion transcript in all 3 confirmed cases and 5 possible cases of synovial sarcoma. Further analysis is still on going for the remaining samples. Conclusion: Molecular detection of SYT-SSX fusion-transcript is useful in establishing the diagnosis of Synovial Sarcoma.